2021
DOI: 10.1177/11207000211022623
|View full text |Cite
|
Sign up to set email alerts
|

No difference in whole-blood metal ions between 32-mm and 36- to 44-mm femoral heads in metal-on-polyethylene total hip arthroplasty: a 2-year report from a randomised control trial

Abstract: Aim: To investigate the effect of femoral head size on blood metal-ion levels caused by taper corrosion in metal-on-polyethylene total hip arthroplasty, comparing 36- to 44-mm heads with 32-mm heads. Methods: In a randomised, controlled, single-blinded trial, 96 patients were allocated to receive either a 32-mm metal head or the largest possible metal head (36–44 mm) that could be accommodated in the thinnest available vitamin E, cross-linked polyethylene insert. Blood metal ion levels were collected at 1- and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The median cobalt and chromium levels for the 28 mm head group were 0.66 μg/L and 0.68 μg/L, respectively. Similarly, no difference was found in cobalt and chromium blood levels in a randomized study comparing 32 mm, 36 mm and 40 mm modular CoCrMo heads at 1‐ and 2‐years follow‐up 33 …”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The median cobalt and chromium levels for the 28 mm head group were 0.66 μg/L and 0.68 μg/L, respectively. Similarly, no difference was found in cobalt and chromium blood levels in a randomized study comparing 32 mm, 36 mm and 40 mm modular CoCrMo heads at 1‐ and 2‐years follow‐up 33 …”
Section: Discussionmentioning
confidence: 93%
“…Similarly, no difference was found in cobalt and chromium blood levels in a randomized study comparing 32 mm, 36 mm and 40 mm modular CoCrMo heads at 1-and 2-years follow-up. 33 Neck taper flexural rigidity also affect trunnion corrosion and one study showed that lower stem flexural rigidity predicted stem fretting and corrosion damage in a ceramic head cohort, but not in the metal head cohort. 23 Care should therefore be taken to generalize the results to different stem designs and materials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation